Genome-wide investigation and expression analysis of OSCA gene family in response to abiotic stress in alfalfa - Li, Xiaohong; Wang, Xiaotong; Ma, Xuxia; Cai, Wenqi; Liu, Yaling; Song, Wenxue; Fu, Bingzhe; Li, Shuxia (Frontiers in Plant Science, 2023)
Alfalfa is an excellent leguminous forage crop that is widely cultivated worldwide, but its yield and quality are often affected by drought and soil salinization. Hyperosmolality-gated calcium-permeable channel (OSCA) proteins are hyperosmotic calcium ion (Ca2+) receptors that play an essential role in regulating plant growth, development, and abiotic stress responses. However, no systematic analysis of the OSCA gene family has been conducted in alfalfa. In this study, a total of 14 OSCA genes were identified from the alfalfa genome and classified into three groups based on their sequence composition and phylogenetic relationships. Gene structure, conserved motifs and functional domain prediction showed that all MsOSCA genes had the same functional domain DUF221. Cis-acting element analysis showed that MsOSCA genes had many cis-regulatory elements in response to abiotic or biotic stresses and hormones. Tissue expression pattern analysis demonstrated that the MsOSCA genes had tissue-specific expression; for example, MsOSCA12 was only expressed in roots and leaves but not in stem and petiole tissues. Furthermore, RT–qPCR results indicated that the expression of MsOSCA genes was induced by abiotic stress (drought and salt) and hormones (JA, SA, and ABA). In particular, the expression levels of MsOSCA3, MsOSCA5, MsOSCA12 and MsOSCA13 were significantly increased under drought and salt stress, and MsOSCA7, MsOSCA10, MsOSCA12 and MsOSCA13 genes exhibited significant upregulation under plant hormone treatments, indicating that these genes play a positive role in drought, salt and hormone responses. Subcellular localization results showed that the MsOSCA3 protein was localized on the plasma membrane. This study provides a basis for understanding the biological information and further functional analysis of the MsOSCA gene family and provides candidate genes for stress resistance breeding in alfalfa.